Electrolyzed water as a green cleaner: chemical and physical characterization at different electrolysing parameters - Khalid, Nurul Izzah; Sulaiman, S.; Ab. Aziz, Norashikin; Taip, Farah Saleena; Sobri, Hafreeza; Mahmud @ Ab Rashid, Nor Khaizura (Rynnye Lyan Resources, 2018)
The aims of this study were to develop electrolysed technique and evaluate the characteristics and performance of electrolysed water that will be applied as a cleaning medium in the food industry. Acidic electrolyzed water (AcEW) and neutral electrolyzed water (NEW) have been reported to have a strong bactericidal effect on various types of foodborne pathogens for many types of food products and food equipment surfaces. While alkaline electrolyzed water (AlEW) is a potential cleaning medium for alkaline wash. The shelf life of electrolyzed water generated from the lab-scale electrolyzing unit was investigated to obtain the best quality electrolyzed water for a long duration. The electrolyzed water was stored in closed dark-brown glass bottles at room temperature. Effect of electrolyzing parameters (electrode type, NaCl concentration, electrical voltage and electrolysis time) on chemical and physical properties (pH, oxidation-reduction potential (ORP), total chlorine, free chlorine, dissolved oxygen) of electrolyzed water (alkaline, acidic, and neutral electrolyzed water) were studied. The chemical and physical properties of electrolyzed water were measured after 24 hrs. Results showed that as time increased, the chemical and physical properties of electrolyzed decreased and eventually reduced the electrolyzed water quality. Freshly prepared electrolyzed water is suggested for cleaning application in food industry. The usage of electrolyzed water is expected to help the food industry in achieving a hygienic environment in their factory and at the same time minimizing the cleaning cost.